RELATIONSHIP BETWEEN ANXIETY LEVELS AND SLEEP QUALITY OF ASTHMATICS - Sri Sumarni (Journal of Innovation Research and Knowledge, 2022)
Asthma is a chronic airway disease that is found throughout the world with varying frequency associated with increased airway sensitivity that triggers episodes of repeated wheezing, shortness of breath, chest tightness, dyspnea and coughing. (cough) especially at night or early morning. Anxiety can also be a heavy burden that causes the individual's life to always be under the shadow of prolonged anxiety and considers anxiety to be a mental strain accompanied by a disturbance in a person's sleep patterns that can easily change or experience a sleep disorder as a result of anxiety in his sick condition or hospital routine. The purpose of this study was to determine the relationship between Anxiety Levels and Sleep Quality of Asthmatics. The design of this study used the Correlational Cross Sectional Analytic method with Non Probality Sampling technique with Quota Sampling type, with a population of 25 patients with asthma and a total sample of 25 people, while data collection using interviews guided by a questionnaire. Results are presented in tabular and narrative form. The results of the study the relationship between anxiety levels with sleep quality of asthmatics indicates that there is a very strong relationship between anxiety levels and sleep quality in asthma patients in Moncek puskesmas with a correlation coefficient of 0.664 with a significance (p value) of 0,000. Seeing the results of this study it is recommended for the health center to be able to create a comfortable environment, especially to limit the skating or drapery in the patient's room and to limit the patient's visit time so that the patient's sleep is not disturbed.